2010
DOI: 10.1590/s1413-70542010000500028
|View full text |Cite
|
Sign up to set email alerts
|

Composição e estabilidade lipídica da farinha de espinhaço de tilapia

Abstract: RESUMOEspinhaços de tilápias (Oreochromis niloticus) são partes do peixe de composição desconhecida. A composição lipídica dos espinhaços não é citada na literatura, bem como a estabilidade da farinha do espinhaço durante o armazenamento. Nesse sentido, realizou se estudo de processamento dos espinhaços envolvendo etapas de cocção, trituração, secagem, peneiramento e armazenamento da farinha. A farinha ficou armazenada sob refrigeração por um período de 90 dias, sendo sua qualidade monitorada por meio da compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 8 publications
5
26
0
5
Order By: Relevance
“…The same was observed for the sum of polyunsaturated fatty acids (Pufa) and for the sum of n-3 series fatty acids (Table 3). Petenuci et al (2010) found a total of 24 fatty acids in tilapia carcass meal, and likewise this study, the predominant fatty acid was oleic acid (18:1n-9), with 35.15%, followed by palmitic (16:0) and linoleic (18:2n-6) acids, with contents of 27.4 and 11.82%, respectively. These fatty acids were also predominant in the lipid fraction of tilapia-head meals (Stevanato et al, 2007).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The same was observed for the sum of polyunsaturated fatty acids (Pufa) and for the sum of n-3 series fatty acids (Table 3). Petenuci et al (2010) found a total of 24 fatty acids in tilapia carcass meal, and likewise this study, the predominant fatty acid was oleic acid (18:1n-9), with 35.15%, followed by palmitic (16:0) and linoleic (18:2n-6) acids, with contents of 27.4 and 11.82%, respectively. These fatty acids were also predominant in the lipid fraction of tilapia-head meals (Stevanato et al, 2007).…”
Section: Resultssupporting
confidence: 81%
“…The highest protein content and the lowest ash content were observed for tuna meal, which can be explained due to the use of fish torsos in the meal elaboration, once these torsos showed more meat and fewer bones, when compared to carcasses used in the other meals. Petenuci et al (2010), were 14.2% moisture, 40.8% protein content, 18.3% ash, and for lipid content was 25.3%. In the present study, the tilapia carcass meal presented higher contents of ash and protein.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Tilapia fishbone flour registered values of 14.2% moisture, 40.8% crude protein, 25.3% total lipids, and 18.3% fixed mineral residues (Petenuci et al, 2010). According to Franco et al (2013), flour from tilapia carcasses provided 2.5% moisture, 45.32% crude protein, 6.93% ether extract, and 38.03% ashes.…”
Section: Resultsmentioning
confidence: 98%
“…Similar to fish meat, the processing of alligator carcasses produces a great amount of residues that are normally directed to animal feed. However, they may also be used in food for human consumption (Stevanato et al, 2007;Franco et al, 2009;Petenuci et al, 2010;Godoy et al, 2013) by including them in several food products. Due to the nutritional quality of the prime matter, the manufacture of flours from the carcasses of the Pantanal alligator may add value to the production chain of the species.…”
Section: Introductionmentioning
confidence: 99%